Desarrollo de una metodología para certificación de tableros eléctricos de baja tensión de acuerdo a la norma IEC 61439 de la empresa cames de Colombia S.A.S - Escarraga Fino, Willinton; Vásquez de moya, Ramiro (Universidad Antonio Nariño, 2022)
The IEC 61439 is a model defined by the International Electrotechnical Commission which is in charge of regulating the distribution and control low voltage energy equipment; this model is oriented to the improvement and manufacturing of electrical assembly fully attached and their components according to every aspect, specifications, metalmechanical characteristics, electrical operational equipment to the point of packaging, transportation, storage and installation. IEC 61439 model is viable for low voltage boards under 1000V in alternating current voltage or 1500V direct current voltage which purpose is to guarantee safety during installation, staff related with this, reduction to the lowest point of internal failures, standardization in assembly variables, emphasizing in maintenance accessibility with the possibility to intervene the set and/or the energized board. The purpose of this document look for implementing a guide of certification that presents in a clear and accurate way the procedure by CAMES DE COLOMBIA S.A.S the systematical development for manufacturing of a set and/or board accomplishing the IEC 61439 model. The making of this certification is the result of the validation of its components; materials resistance associated to environment conditions for their location and installation, characteristics of isolating materials, mechanical impact IK, and protection level IP and electromagnetical compatibility. Thus, the document specifies the rest of the characteristics that determine the electrical board according to the IEC 61439, making the tests, verifying the design and calculation. The project present the instructions for the making of the certification of the boards, presenting the procedure to follow according to the characteristics and demanding of the component to manufacture, from the data or given recquirements by the final user